Mapping the interface between calmodulin and MARCKS-related protein by fluorescence spectroscopy - Ulrich, Andreas (The National Academy of Sciences, 2000)
MARCKS-related protein (MRP) is a myristoylated protein kinase C substrate that binds calmodulin (CaM) with nanomolar affinity. To obtain structural information on this protein, we have engineered 10 tryptophan residues between positions 89 and 104 in the effector domain, a 24-residue-long amphipathic segment that mediates binding of MRP to CaM. We show that the effector domain is in a polar environment in free MRP, suggesting exposure to water, in agreement with a rod-shaped structure of the protein. The effector domain participates in the binding of MRP to CaM, as judged by the dramatic changes observed in the fluorescent properties of the mutants on complex formation. Intermolecular quenching of the fluorescence emission of the tryptophan residues in MRP by selenomethionine residues engineered in CaM reveals that the N-terminal side of the effector domain contacts the C-terminal domain of CaM, whereas the C-terminal side of the effector domain contacts the N-terminal domain of CaM. Finally, a comparison of the fluorescent properties of the myristoylated and unmyristoylated forms of a construct in which a tryptophan residue was introduced at position 4 close to the myristoylated N terminus of MRP suggests that the lipid moiety is also involved in the interaction of MRP with CaM.